Brève histoire de la paroisse des Saints-Anges, 1676-2001 - Robichaud, André; Lamarche, Hélène; Dumont-Frenette, Geneviève (Société d'histoire de Lachine, 2001)
Keywords: Lachine

Entre les Pays-d'en-Haut et Montréal: le lieu-dit Lachine - Vaillancourt, Pascale (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine

Étude historique du développement urbain. L’axe du canal de Lachine – partie Lachine et LaSalle - Poitras, Claire; Aubry, Jean-Christian (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2004)
Keywords: Lachine (canal)

History's Floodgate: The Lachine Canal Reopens - Gedeon, Julie (The Beaver, 2002)
Keywords: Lachine (canal)

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal)

Le canal de Lachine: les métamorphoses d’un quartier - Bélisle, Jean (Continuité, 2003)
Keywords: Lachine (canal)

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
Keywords: Lachine (canal)

Moments d’histoire à Lachine - Buteau, Hélène (Continuité, 2001)
Keywords: Archéologie; Lachine

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Understanding the Built Form of Industrialization along the Lachine Canal in Montreal - Bliek, Desmond; Gauthier, Pierre (Urban History Review / Revue d'histoire urbaine, 2006)
Keywords: Lachine (canal)

Les paysages urbains historiques des canaux de Lachine et de Chambly: une démarche exploratoire. - Gelly, Alain; Paradis, Mathieu (Paysages du mouvement/paysages en mouvements: Trajectoires, perspectives et panoramas, 2021)
Keywords: Lachine (canal)

Étude historique du développement urbain. L’axe du canal de Lachine – partie Sud-Ouest - Poitras, Claire; Bérubé, Harold (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2004)
Keywords: Lachine (canal)

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

From Meritocracy to Seniority: Shifting Masculine Aesthetics Among blue-collar workers in Montréal Lachine - Desforges, Exan Yuen (Université Concordia, 2008)
Keywords: Lachine; Quartiers

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Keywords: Lachine (canal); Paysages

Fourrures, eau-de-vie et absolution: réseaux sociaux, économiques et politiques à Lachine, 1670-1680 - Martin, Catherine (Université de Sherbrooke, 2014)
Keywords: Fourrure; Lachine

Aviron Lachine Rowing. 1863-2013: A History - Cabana, Richard (Richard Cabana, 2015)
Keywords: Clubs

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

Évaluation du patrimoine urbain: arrondissement de Lachine - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Lachine; Patrimoine

The Lachine Canal: Riding the Waves of Industrial and Urban Development, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Keywords: Lachine (canal); Énergie hydraulique

Le canal de Lachine: du tumulte des flots à l'essor industriel et urbain, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Keywords: Lachine (canal); Énergie hydraulique

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

L'histoire d'une communauté vivante, 1676-2009 - Nichol, Bonnie; Nichol, Ron (Bonnie Nichol et Ron Nichol, 2010)
Keywords: Lachine

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
Keywords: Lachine (canal); Montreal Rolling Mills

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

Marriage index: Saint Andrew's Presbyterian Church, Lachine, 1818-1925 - Dunn, Robert (Quebec Family History Society, 2006)
Keywords: Lachine; Mariage; Presbytériens; Protestants; Registres

Pour une approche urbanistique de la conservation et de la mise en valeur du patrimoine bâti: l’expérience du canal de Lachine à Montréal - Payette-Hamelin, Mathieu (Université de Montréal et Université Paul Cézanne, 2011)
Keywords: Conservation; Lachine (canal); Patrimoine

Les minoteries du canal de Lachine - Gelly, Alain (Cap-aux-Diamants, 2021)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie flour Mills

Un essor laborieux : l'électricité et le monde industriel. Les choix énergétiques des entrepises du canal de Lachine, Montréal, 1880-1920 - Gelly, Alain (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

Enjeux de redéveloppement et morphologie urbaine aux abords du canal de Lachine: Petite-Bourgogne et Pointe-Sainte-Charles - Gildas, Michel (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2000)
Keywords: Lachine (canal); Petite-Bourgogne; Pointe-Saint-Charles; Quartiers

D'audace en mémoire: le lieu dit Lachine, un regard archéologique - Buteau, Hélène; Chevrier, Daniel (In Situ, 2001)
Keywords: Lachine; Le Ber, Jacques; Le Moyne de Longueuil, Charles; Maison LeBer-LeMoyne

Analyse des processus de recherche et de modélisation du patrimoine à partir de deux cas: l'écluse Saint-Gabriel du canal de Lachine et la gare Montreal and Southern Counties Railways Co. - Gosselin, Louis Pierre (Université de Sherbrooke, 2014)
Keywords: Chemins de fer; Gares; Lachine (canal); Navigation; Patrimoine

Musée de Lachine, Montréal. Arrondissement Lachine. Maison LeBer-LeMoyne, BiFk-6. Interventions archéologiques 2009. Rapport - Archéotec inc. (Ville de Montréal et Ministère de la Culture, des Communications et de la Condition féminine, 2011)
Keywords: Lachine; Le Ber, Jacques; Le Moyne de Longueuil, Charles; Logement; Maison LeBer-LeMoyne; Marchands

L'axe du canal de Lachine et les quartiers du Sud-Ouest. Grandeur et misère du berceau de l'industrialisation du pays? - Poitras, Claire (Montréal : la cité des cités, 2017)
Keywords: Arrondissements; Côte-Saint-Paul; Griffintown; Groupes populaires; Lachine (canal); Le Sud-Ouest (arrondissement); Patrimoine; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Saint-Henri; Ville Émard

Brève histoire de la paroisse des Saints-Anges, 1676-2008 - Robichaud, André; Lamarche, Hélène; Dumont-Frenette, Geneviève (Société d'histoire de Lachine, 2008)
Keywords: Lachine

L'Hôpital de Lachine célèbre son centenaire en 2013 / The Lachine Hospital Celebrates its 100th Anniversary in 2013 (Héritage Dorval, 2013)
Keywords: Hôpitaux

L'escadrille 686 Dorval/Lachine célèbre son 65e anniversaire de fondation/686 squadron Dorval/Lachine celebrates its 65th anniversary - Hébert, Michel (Héritage Dorval, 2023)
Keywords: Aviation; Dorval

Essai de synthèse ethnohistorique du secteur des Rapides de Lachine. Rapport final - Des Roches, Jacques (Communauté urbaine de Montréal, Service de la mise en valeur du territoire, Division de l'aménagement, 2001)

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

Vestiges industriels montréalais: appropriations, rôles et enjeux sociaux - Bélanger, Michelle (Université de Montréal, 2011)
Keywords: Lachine (canal); Patrimoine

Quatre filles fondatrices - Nantel Bergeron, Dominique (Histoire Québec, 2024)
Keywords: Famille; Femmes; Lachine

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Urban Occupations Urbaines: Curating the Post-industrial Landscape - Janssen, Shauna (Université Concordia, 2014)
Keywords: Gentrification; Griffintown; Lachine (canal); Patrimoine; Quartiers

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

Élites commémorantes et mise en scène de l’histoire dans la construction de l’identité lachinoise à l’époque du maire Anatole Carignan (1933-1939 et 1944-1952) - Gravel, Denis (Université de Montréal, 2018)
Keywords: Commémoration; Conseillers municipaux; Fonctionnaires; Histoire; Lachine; Maires

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Montréal hanté: la mémoire macabre d'une cité victorienne - Baril, Pierre-Luc (VLB éditeur, 2024)
Keywords: Cimetières; Guibord, Joseph; Lachine (canal); Photographie; Pied-du-Courant; Redpath (musée); Épidémies

Mouvement syndical et mobilisation pour l’emploi: renouvellement des enjeux et des modalités d’action - Fontan, Jean-Marc; Klein, Juan-Luis (Politique et sociétés, 2000)
Keywords: Confédération des syndicats nationaux; Dominion Bridge; Fédération des travailleurs et travailleuses du Québec (FTQ); Lachine

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Montréal au fil du temps - McQuarrie, John; Demers, Jacques (Magic Light Publishing, 2002)
Keywords: Hôtel de ville; Jardin botanique; Lachine (canal); Mont Royal; Places publiques; Pointe-à-Callière; Rues; Squares; Églises

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

L'économie montréalaise au XIXe siècle - Labrecque, Annie-Claude; Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

The Montreal Economy during the Nineteenth Century - Fougères, Dany; Labrecque, Annie-Claude (Montreal: The History of A North American City, 2018)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime